41 Vascular protein oxidation and redox proteomics in human hypertension. (17th November 2015) - Tsiropoulou, S; Montezano, AC; Scott, A; Burchmore, RJ; Touyz, RM
Abstract : Despite recent advances in the field of vascular redox signalling in hypertension, it still remains unclear exactly how ROS cause vascular injury. We hypothesise that regulation of redox-sensitive protein tyrosine phosphatases (PTP) through oxidative modification, is impaired in hypertension. VSMC normotensive (NT) and hypertensive (HT) individuals were stimulated with AngII (10-7 M) and ET-1 (10-7 M). Irreversible oxidation of proteins and PTPs was assessed by oxyblot. Differential gel electrophoresis (DiGE) and CyDye thiol labelling were employed for screening of reversibly oxidised proteome. Irreversible protein oxidation was not affected by AngII or ET-1 in VSMCs from NT and HT subjects. Proteomic data, filtered for FC >2, detected 2051 spots with 1899 (92.5%) being equally oxidised between NT and HT. In addition, oxidation of 57 (2.9%) spots was increased, while 95 (4.6%) were decreased in HT. Candidate proteins exhibiting consistent changes across three experimental replicates included β-actin (FC = –2.86), annexin A1 (–2.23), galectin-1 (–1.67), FK506 binding protein (–2.35) and polymerase I and transcript release factor (PTRF, –1.92). Stimulation with AngII altered the redox status in 2–3% of proteins, both in HT and NT. However, vimentin was the only target changing consistently across the replicates (FC = 2.48). Our findings indicate that pro-hypertensive agents may not impact significantly on irreversible protein and PTP oxidation in health and disease, but may have effects on reversible oxidation. Our proteomic data, in agreement with our previous rat studies, support decreased reversible thiol oxidation in hypertension.